MEMBACA URGENSI MODERASI DALAM MADĪNAH AL-FĀḌILAH AL-FARĀBI: STUDI WACANA PEMBANGUNAN BERKELANJUTAN DI INDONESIA - Nurul Khair; Nuri Barezatul Bilqis; Panji Perdana Putra Priyanto; Sayyida Sayyida; Farid Hamdani (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2022)
This paper is a literature review of Al-Farābi's thoughts on the urgency of the value of moderation in the discourse of sustainable development in Indonesia which is studied through his magnumopus entitled "Madīnah Al-Fāḍilah". By using a descriptive-analytical approach, it is concluded that the value of moderation is the main basis for understanding the role and existence of individuals to actualize a variety of sustainable development through the implementation of the 4 pillars of moderation in Al-Farābi's view, namely unity, deliberation, mutual cooperation, and character. The four pillars of moderation in Al-Farābi's view seek to build the closeness of each individual in social life, in order to discuss solving various problems that hinder the factors of sustainable development. The implementation of the 4 pillars of moderation in Al-Farābi's view can be realized through the existence of a leader as an existence that influences the paradigm and behavior of people in a region. That is, leaders are here to unite people of various groups to realize their role and position in order to optimize the value of moderation as the basis for sustainable development in reality. The final result of this paper is to understand the application of Al-Farābi's value of moderation in welcoming sustainable development in Indonesia.